2019
DOI: 10.1186/s13014-019-1219-y
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation and bone quality: time-dependent effects

Abstract: BackgroundThe aim of this study was to evaluate the ionizing radiation (IR) effects on rat bone 30 and 60 days after irradiation.MethodsWistar rats were submitted to IR (30 Gy) on the left leg and were euthanized after 30 and 60 days. The legs were divided into four groups according to the treatment and euthanization time: C30 and C60 (right leg–without IR), IR30 and IR60 (left leg-with IR).ResultsCT analysis showed more radiodensity in C60 compared with other groups, and IR60 showed more radiodensity than IR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Some studies have shown that irradiation increases plastic deformation in bone tissue by releasing free radicals via radiolysis of water molecules, degrading collagen molecules and restricting fibrillary sliding mechanisms, 29 , 30 which affect the proper molecular arrangement for the biomineralization process to occur. 16 In addition, irradiation may affect the activity of osteoblasts in terms of normal deposition and development of hydroxyapatite crystals from the inorganic matrix. 29 , 30 The secondary effect caused by ionizing radiation is related to the implant composition, and we agree that the implant composition is decisive for the bone response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that irradiation increases plastic deformation in bone tissue by releasing free radicals via radiolysis of water molecules, degrading collagen molecules and restricting fibrillary sliding mechanisms, 29 , 30 which affect the proper molecular arrangement for the biomineralization process to occur. 16 In addition, irradiation may affect the activity of osteoblasts in terms of normal deposition and development of hydroxyapatite crystals from the inorganic matrix. 29 , 30 The secondary effect caused by ionizing radiation is related to the implant composition, and we agree that the implant composition is decisive for the bone response.…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is one of the most common treatments for head and neck cancer patients, 4 , 13 and ionizing radiation can reduce bone healing capacity through the progressive fibrosis of blood vessels and soft tissue, 14 loss of osteoblast function 15 and damage to the collagen arrangement. 16 These effects can also negatively influence bone/implant integration. 5 , 10 Studies have been carried out to evaluate implant survival in previously irradiated areas, 2 , 3 , 5 but there are limited data on the effect of backscattered radiation on the osseointegration process of implants placed before ionizing radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Limirio et al, [15] Ionising radiation and bone quality: time dependent effects Bartlow et al, [16] Limited field radiation therapy results in decreased bone fracture toughness in a murine model Wright et al, [17] Single-limb irradiation induces local and systemic bone loss in a murine model Barbosa et al, [18] Effect of ionising radiation after-therapy interval on bone: histomorphometry and biomechanical characteristics Oest et al, [19] Longitudinal effects of single hindlimb radiation therapy on bone strength and morphology at local and contralateral sites Sullivan et al, [20] A mouse model for skeletal structure and function changes caused by radiation therapy and oestrogen deficiency Lima et al, [21] Exposure to low-dose X-ray radiation alters bone progenitor cells and bone microarchitecture Zhai et al, [22] Influence of radiation exposure pattern on the bone injury and osteoclastogenesis in a rat model volume and microarchitecture using μCT. The right hindlimb represents the irradiation sides compared to the left hindlimb (contralateral-shielded bone) and control bone.…”
Section: Author Years Titlesmentioning
confidence: 98%
“…These injuries lead to impairment in bone repair properties that could progress to complications, such as infections, healing delay and osterradionecrosis (3). Previous publicatios from our group showed the effects of RT on cortical bone that revealed modification on the morphology of bone channels network (4), decreased anisotropy and increased bone fragility (5), also with deficity in bone quality, with decrease of stiffness, more evident in later time points after radiation (6).…”
Section: Introductionmentioning
confidence: 94%